ACCOUNTING INFORMATION SUPPORT ANALYSIS AND DIAGNOSIS (BANKRUPTCY) ORGANIZATIONS - Tatiana Khmelnytskaya; Andrey Oleynikov (Вестник Северо-Кавказского федерального университета, 2022)
The article discusses the relevance and the need to improve accounting and information support for the analysis and prevention of bankruptcy of an economic entity by allocating levels of information system typing information source groups in order to increase the credibility and reliability of data in the process of independent oversight.